Ekonomi Kreatif : Pelatihan Pembuatan Buket Kreatif sebagai Inovasi Bisnis Pemula bagi Remaja Dusun Lilin - Ni Nengah Ayu Wulandari; I Ketut Putu Suardana; Ida Ayu Nyoman Widia Laksmi; I Komang Widya Purnama Yasa (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
The lack of entrepreneurial skills among rural youth poses a challenge in creating local employment opportunities. The creative bouquet-making training serves as an effort to foster an entrepreneurial spirit and develop the creative economy at the local level. This activity was carried out in Dusun Lilin, Giri Tembesi Village, as a form of community service aimed at promoting the economic empowerment of young people in the digital era. The main objective of this program was to equip 20 youth participants with technical skills in bouquet arrangement, foster creativity, and introduce simple digital marketing strategies through social media. The implementation methods included observation, material delivery, hands-on practice, and simple evaluations through pretests and posttests. The results showed an 85% improvement in technical skills based on evaluation outcomes, along with increased participants’ confidence in producing aesthetically and economically valuable products. In addition, participants were able to understand business opportunities from the products they created and learned how to market them digitally. Thus, this activity not only strengthened individual skills but also had a positive impact on the sustainable development of the local creative economy.